Is the Number of Different MRI Findings More Strongly Associated with Low Back Pain Than Single MRI Findings? - Hancock, M.; Kjaer, P.; Kent, Peter; Jensen, R.; Jensen, T. (Lippincott, Williams and Wilkins, 2017)
Study design: A cross-sectional and longitudinal analysis using two different datasets. Objective: To investigate if the number of different magnetic resonance imaging (MRI) findings present is more strongly associated with low back pain (LBP) than single MRI findings. Summary of Background Data: Most previous studies have investigated the associations between single MRI findings and back pain rather than investigating combinations of MRI findings. If different individuals have different pathoanatomic sources contributing to their pain, then combinations of MRI findings may be more strongly associated with LBP. Methods: This study used data from two previous studies that investigated the association between single MRI findings and LBP. One study was a cross-sectional population cohort of 412 people of 40 years; the second was a longitudinal cohort of 76 people recently recovered from LBP who were followed for 12 months. The outcome for the cross-sectional study was presence of LBP during the last year. The outcome for the longitudinal study was days to recurrence of activity limiting LBP. In both datasets, we created an aggregate score of the number of different MRI findings present in each individual and assessed the relationship between this aggregate score and LBP. Results. The risk of LBP outcome increased with increasing numbers of different MRI findings. Compared with those with no MRI findings, those with three MRI findings were at substantially greater risk of LBP in the last year (odd ratio ¼ 14.1; 95% confidence interval, 4.32–49.47) in the cross-sectional study, or of future recurrence of LBP (hazard ratio ¼ 12.2; 95% confidence interval 1.26–118.21) in the longitudinal study. Conclusion: The aggregate MRI score was more strongly associated with LBP outcomes than single MRI findings in both datasets. Further investigation of this approach is indicated.